Effective photocatalytic initiation of reactive oxygen species by a photoactive covalent organic framework for oxidation reactions - Li, Yangyang (2022)
Reactive oxygen species (ROS) play a vital role in both chemistry and physiology. Developing effective photocatalysts becomes a feasible approach to trigger the generation of ROS. Herein, a photosensitive covalent organic framework (COF) was rationally designed and constructed by incorporating the photoactive triphenylamine moieties into its skeleton, characterizations of which not only showed the success formation of the highly crystalline and stable framework, but also revealed the photoactive property derived from triphenylamine-based building block. Electron paramagnetic resonance measurements displayed that the COF was an effective photocatalyst for generating ROS with one unpaired electron, that is, superoxide radical anion (O2•-). Subsequently, its high efficiency, selectivity, and reusability in photocatalytic aerobic oxidation of sulfides confirmed that the COF is a promising photocatalyst in the applications of ROS-involved reactions, demonstrating that precisely embedding organic photochromic groups into COFs could be a powerful strategy to fabricate metal-free heterogeneous photocatalysts for targeted reactions.